2020
DOI: 10.1016/j.sleep.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' postpartum sleep disturbance is associated with the ability to sustain sensitivity toward infants

Abstract: Infancy is a period of rapid development when the quality of caregiving behavior may be particularly consequential for children's long-term functioning. During this critical period for caregiving behavior, parents experience changes in their sleep that may affect their ability to provide sensitive care. The current study investigated the association of mothers' sleep disturbance with both levels and trajectories of maternal sensitivity during interactions with their infants. At 18 weeks postpartum, mothers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 78 publications
1
24
1
Order By: Relevance
“…The disagreements between self-report (e.g., daily diaries) and objective measurements (e.g., actigraphy) of sleep have been reported across several studies, and these discrepancies may be due to potential biases in individuals’ subjective estimate of sleep (Girschik et al, 2012; Jackson et al, 2020). Indeed, King et al (2020) found no association between maternal subjective sleep (i.e., nighttime sleep duration, number of night wakings, wake time after sleep onset, and perceived sleep quality) and maternal sensitivity toward infants during free-play interaction. However, they found actigraphic sleep continuity but not sleep duration to be predictive of changes in maternal sensitivity during interactions.…”
Section: Parent Sleep and Parenting Qualitymentioning
confidence: 86%
“…The disagreements between self-report (e.g., daily diaries) and objective measurements (e.g., actigraphy) of sleep have been reported across several studies, and these discrepancies may be due to potential biases in individuals’ subjective estimate of sleep (Girschik et al, 2012; Jackson et al, 2020). Indeed, King et al (2020) found no association between maternal subjective sleep (i.e., nighttime sleep duration, number of night wakings, wake time after sleep onset, and perceived sleep quality) and maternal sensitivity toward infants during free-play interaction. However, they found actigraphic sleep continuity but not sleep duration to be predictive of changes in maternal sensitivity during interactions.…”
Section: Parent Sleep and Parenting Qualitymentioning
confidence: 86%
“…Also, maternal sleep quality may cause problems with parenting quality. King et al [33] have reported that mothers with poorer sleep continuity have decreased sensitivity toward their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a family systems perspective, individuals’ sleep problems have been linked with multiple aspects of family functioning (e.g., marital conflict; El-Sheikh & Kelly, 2017; McHale et al, 2017). With specific regard to parenting, several important studies have examined sleep and functioning of mothers of infants (e.g., Bai et al, 2019; King et al, 2020). Suprisingly limited work has considered children after infancy, nevertheless existing findings are compelling and indicate that sleep problems exacerbate risk for negative parenting behaviors.…”
Section: Current Studymentioning
confidence: 99%